2021
DOI: 10.5194/nhess-21-1355-2021
|View full text |Cite
|
Sign up to set email alerts
|

Fatalities associated with the severe weather conditions in the Czech Republic, 2000–2019

Abstract: Abstract. This paper presents an analysis of fatalities attributable to weather conditions in the Czech Republic during the 2000–2019 period. The database of fatalities deployed contains information extracted from Právo, a leading daily newspaper, and Novinky.cz, its internet equivalent, supplemented by a number of other documentary sources. The analysis is performed for floods, windstorms, convective storms, rain, snow, glaze ice, frost, heat, and fog. For each of them, the associated fatalities are investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…A similar gap in weather impact reports also appeared around and after the political change in the country, when media concentrated rather on the formation of a new democratic society. But as mentioned in detail by Br azdil et al (2021a), also after 1990 we may see changes in weather impacts information depending on the media market, strategy and internal changes in the actual newspaper.…”
Section: Discussionmentioning
confidence: 98%
“…A similar gap in weather impact reports also appeared around and after the political change in the country, when media concentrated rather on the formation of a new democratic society. But as mentioned in detail by Br azdil et al (2021a), also after 1990 we may see changes in weather impacts information depending on the media market, strategy and internal changes in the actual newspaper.…”
Section: Discussionmentioning
confidence: 98%
“…For CZE, both databases include three FEs that took place during the period under review, with FFEM-DB having 5% more FFs 59 , 60 .…”
Section: Technical Validationmentioning
confidence: 99%
“…Rainstorms are severe weather phenomena, and a series of accidents can occur because of a rainstorm. Brazdil et al [ 14 ] reported that rain led to 205 fatalities in the Czech Republic from 2000 to 2019, and the results showed that nearly half of the fatalities (49.8%) occurred in the summer months. Tobin et al [ 15 ] estimated the relative risk of crashes during rain using a matched-pair analysis in Kansas for 1995–2014.…”
Section: Introductionmentioning
confidence: 99%
“…Rainstorms can lead to a series of secondary disasters, such as flash floods, landslides, mudslides, house collapses, and traffic and communication interruptions, which can bring serious harm to the national economy and people’s lives and property. Previous studies have mainly focused on the accidents caused by rainstorms [ 14 , 15 , 16 ], but they have failed to conduct a deep analysis of the causes, consequences, and prevention measures of these accidents. Preliminary hazard analysis (PHA) [ 17 , 18 ], fault tree analysis (FTA) [ 19 , 20 ], and bow-tie models [ 21 , 22 ] are widely used to identify the causes, consequences, and prevention measures for fatal accidents, and the results have shown that these methods can obtain accurate accident data and reduce the risk of accidents.…”
Section: Introductionmentioning
confidence: 99%